The Prevalence of Refractive Errors Among Online Motorcycle Taxi Drivers in Pondok Aren, 2025 - Putra, Dian; Hudyono, Johannes; Simatupang, Aswin Oktavian Hasudungan (Universitas Kristen Krida Wacana, 2025)
Refractive errors are visual impairments that can reduce quality of life and occupational safety, particularly in online motorcycle taxi drivers who rely heavily on visual acuity. A lack of routine eye examinations often leads to undetected conditions. To determine the prevalence of refractive errors and their distribution based on gender, age, and type of refractive error among online motorcycle taxi drivers. This study used a descriptive cross-sectional design. A total of 120 respondents were selected using stratified random sampling based on age groups. Visual acuity was assessed using a Snellen chart and trial lenses. The majority of respondents were male (83.3%) and aged 20–30 years (40%). The most common refractive error in the right eye was compound myopic astigmatism (28.3%), while in the left eye it was myopia (22.5%). Refractive errors are commonly found among online motorcycle taxi drivers, with combination types such as compound myopic astigmatism being the most dominant.